Correlation between Relative Humidity and Forest Seeds Moisture on the Incidence of Fungi - Adriana Antonio Bautista; José Luis Arispe Vázquez; Mario Ernesto Vázquez Badillo; Armando Rodríguez García; Luis Alberto Aguirre Uribe; Agustín Hernández Juárez; Epifanio Castro-Del Ángel; Juan Mayo Hernández (International Journal of Forestry Research)
The objective of the research was to evaluate the effect of relative humidity (RH) and moisture content (MC) on the incidence of pathogenic fungi on the seeds of Agave lechuguilla, Lippia graveolens, and Nolina cespitifera. Seeds were stored 90 days at 60, 75, 80, and 85% RH, and results were processed with a correlation analysis in the R software using the Spearman test. Higher fungi incidence (FI) in seeds was found from 10 to 20% RH; however, correlation between RH and MC of seeds was positive with r = 0.311 and p=2.2×10−16. In general, RH is related to MC, but not to fungi incidence, which is related mainly to MC of seeds. Correlation between RH and FI for each seed species was not significant, r = 0.026, −0.040, and 0.071 and p=0.687, 0.540, and 0.272 for A. lechuguilla, N. cespitifera, and L. graveolens, respectively. There was a positive correlation between the MC of seeds with fungi incidence; a negative correlation between the RH and the FI; and a positive correlation between the RH and the MC of seeds. In this type of seeds (orthodox), the MC is probably the most important factor in determining its longevity. The seeds under study can be stored in a 60% to 75% RH. Five fungi genera were found, predominating Aspergillus with five identified species.